Intergenerational transmission of emotion dysregulation: Part I. Psychopathology, self-injury, and parasympathetic responsivity among pregnant women. (August 2019) - Lin, Betty; Kaliush, Parisa R.; Conradt, Elisabeth; Terrell, Sarah; Neff, Dylan; Allen, Ashley K.; Smid, Marcela C.; Monk, Catherine; Crowell, Sheila E.
Abstract: The World Health Organization recently reported that maternal mental health is a major public health concern. As many as one in four women suffer from psychiatric disorders at some point during pregnancy or the first postpartum year. Furthermore, self-injurious thoughts and behaviors (SITBs) represent one of the leading causes of death among women during this time. Thus, efforts to identify women at risk for serious forms of psychopathology and especially for SITBs are of utmost importance. Despite this urgency, current single-diagnostic approaches fail to recognize a significant subset of women who are vulnerable to perinatal stress and distress. The current study was among the first to investigate emotion dysregulation—a multilevel, transdiagnostic risk factor for psychopathology—and its associations with stress, distress, and SITBs in a sample of pregnant women (26–40 weeks gestation) recruited to reflect a range of emotion dysregulation. Both self-reported emotion dysregulation and respiratory sinus arrhythmia, a biomarker of emotion dysregulation, demonstrated expected associations with measures of mental health, including depression, anxiety, borderline personality pathology, and SITBs. In addition, self-reported emotion dysregulation was associated with blunted respiratory sinus arrhythmia responsivity to an ecologically valid infant cry task. Findings add to the literature considering transdiagnostic risk during pregnancy using a multiple-levels-of-analysis approach.